UV Light–inactivated HSV-1 Stimulates Natural Killer Cell–induced Killing of Prostate Cancer Cells. Issue 5 (June 2019) - Samudio, Ismael; Hofs, Elyse; Cho, Brandon; Li, Michael; Bolduc, Kayla; Bu, Luke; Liu, Guoyu; Lam, Vivian; Rennie, Paul; Jia, William; Elisia, Ingrid; Krystal, Gerald
Abstract : Herein we demonstrate that ultraviolet light–inactivated Herpes Simplex Virus-1 (UV-HSV-1) stimulates peripheral blood mononuclear cells (PBMCs) to lyse both androgen-sensitive and androgen-independent prostate cancer (PrCA) cell lines, but not the benign prostatic hyperplastic epithelial cell line, BPH-1, and is 1000–10, 000-fold more potent at stimulating this killing than ultraviolet light-inactivated Vesicular Stomatitis Virus, adenovirus, reovirus or cytomegalovirus. Among PBMCs, natural killer (NK) cells appear to be a major cell type involved in this killing and UV-HSV-1 appears to directly and potently stimulate NK cell expression of CD69, degranulation, cytokine production, and migration to IL-8 in PC3 conditioned medium. We also found that UV-HSV-1 stimulates glycolysis in PBMCs and NK cells, and that 2-deoxyglucose and the protein kinase C inhibitor, Go6976, and the NFκB inhibitor, Bay 11-7082, all abrogate UV-HSV-1 activated killing of PC3 cells by PBMCs and NK cells. Using neutralizing anti-Toll-like receptor 2 (TLR2) we found that UV-HSV-1, like HSV-1, activates NK cells via TLR2. Taken together, these results are consistent with Toll-like receptor 2 ligands on UV-HSV-1 stimulating TLR2 on NK cells to activate protein kinase C, leading to enhanced glycolysis and NFκB activation, both of which play a critical role in this anti-PrCA innate immune response. Importantly, UV-HSV-1 synergizes with IL-15 to increase the cytolytic activity of PBMCs against PC3 cells and there was considerable donor-to-donor variation in killing ability. These results support the preclinical development of UV-HSV-1 as an adjuvant, in combination with IL-15, for cell infusions of healthy, preselected NK cells to treat PrCA. Abstract : Supplemental Digital Content is available in the text.